Penggunaan Fisikal Model dalam Perancangan Arsitektur - Prawata, Albertus (ComTech: Computer, Mathematics and Engineering Applications, 2013)
One important factor in architectural design process that are used is physical model. Information and design solutions for the architectural design process can be obtained using physical model. It is a tool that can be used to visualize the architecture design process from the conceptual to the final design. This paper explains the types and the use of physical model with their characteristics. It also describe information and solutions from the physical model that can be used during the architectural design process.